2016
DOI: 10.1007/s00466-016-1271-5
|View full text |Cite
|
Sign up to set email alerts
|

A geometrical multi-scale numerical method for coupled hygro-thermo-mechanical problems in photovoltaic laminates

Abstract: A comprehensive computational framework based on the finite element method for the simulation of coupled hygro-thermo-mechanical problems in photovoltaic laminates is herein proposed. While the thermo-mechanical problem takes place in the three-dimensional space of the laminate, moisture diffusion occurs in a two-dimensional domain represented by the polymeric layers and by the vertical channel cracks in the solar cells. Therefore, a geometrical multi-scale solution strategy is pursued by solving the partial d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This can be primarily motivated by thermo-mechanical stresses which damage and break the gridline deposited onto solar cells, as observed in the thermal cycling tests for an amount of cycles above 200, plus the accelerated oxidation of the gridline induced by moisture whose diffusion within the encapsulant is accelerated by cracks. As shown in the numerical simulations in Lenarda and Paggi, 38 cracks connect the two layers of the encapsulating material above and below the solar cells and therefore enhance moisture diffusion.…”
Section: Discussionmentioning
confidence: 95%
“…This can be primarily motivated by thermo-mechanical stresses which damage and break the gridline deposited onto solar cells, as observed in the thermal cycling tests for an amount of cycles above 200, plus the accelerated oxidation of the gridline induced by moisture whose diffusion within the encapsulant is accelerated by cracks. As shown in the numerical simulations in Lenarda and Paggi, 38 cracks connect the two layers of the encapsulating material above and below the solar cells and therefore enhance moisture diffusion.…”
Section: Discussionmentioning
confidence: 95%
“…In fact, a further propagation of cracks and an increase of their opening can lead to an expansion of the electrically inactive solar cell areas, with a consequent increase of power-loss [6]. In this regard, the crack pattern with partial electric insulation observed for the soft substrate (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In ANSYS, all the respective material properties of component layers in the PV module are inputted as Engineering Data. Lenarda and Paggi, (2016), proposed a geometrical multi-scale numerical method for coupled hygro-thermo-mechanical problems in photovoltaic laminates. They presented advanced model schemes of imperfect sealing between PV component layer interfaces.…”
Section: Finite Element Modelling and Methodologymentioning
confidence: 99%
“…Kurnik et al (2011) in their outdoor testing of PV module temperature and performance under different mounting and operating conditions, reported that the temperature difference between ambient and module can be as high as 22 °C. The PV module has been described as a layered composite of different materials hence the different material combinations complicate stress distribution and concentration (Lenarda and Paggi, 2016;Ojo and Paggi, 2016a). Operations at high-temperatures increases the mismatch effect among crystalline silicon wafer, silver contacts, solder, copper ribbons and other component layers in the module occasioned by the differences in their coefficient of thermal expansion (CTE).…”
Section: Introductionmentioning
confidence: 99%